A novel view of suprathreshold stochastic resonance and its applications to financial markets - Citovsky, Gui; Focardi, Sergio (Frontiers in Applied Mathematics and Statistics, 2015)
We introduce an original application of Suprathreshold Stochastic Resonance (SSR). Given a noise-corrupted signal, we induce SSR in effort to filter the effect of the corrupting noise. This will yield a clearer version of the signal we desire to detect. We propose a financial application that can potentially reveal big positions in a market. We assume there exist return signals that correspond to big orders, which are hidden by noise from small scale traders. We induce SSR in an attempt to reveal these big positions.